FREQUENCY OF HBeAg POSITIVITY IN CHRONIC HEPATITIS B INFECTED PATEINTS - Mehr, Muhammad Tariq; Khan, Humera; Iman, Noor Ul (Journal of Postgraduate Medical Institute, 2017)
Objective: To determine the frequency of HBeAg positivity in chronic hepatitis B infected patients. Methodology: This descriptive cross-sectional study was carried out for one year between June 01, 2014 till May 30, 2015 in a private consulting clinic at Ibrahimi Hospital, Dabgari Gardens, Peshawar - Pakistan. A total of 149 patients were included in the study. All patients of either gender between 15 to 70 years of age, newly diagnosed with HBV infection in the form of positive HBsAg on third generation ELISA were included in the study. In all the patients, HBeAg was checked. Data were analyzed using SPSS version 20.0. Results: Out of the total 149 patients between 20 to 60 years (mean 41 ±8.7) included in the study, the males 112 (75.2%) outnumbered the females 37 (24.8%). The prevalence of HbeAg in chronic HBV was 28.2 % (males 16.10 %, females 12.08%) with more patients (22.14%) between 21 and 40 years of age. Conclusion: The frequency of HbeAg was found in a significant number of chronic HBV patients. Its frequency was more in males and in the age group of 21 to 40 years.